Contribuições do turismo para a revitalização do rural - Silva, Mirele Milani da (2013)
The rural area is undergoing profound transformations both in the advancement of agricultural modernization, for the activities related to new inside, new roles and expressing itself in different ways in social and economic heterogeneous, thus enabling new revenue and upgrading of the rural, incorporating the use of tangible and intangible assets. In this space, new ruralities arises rural tourism, an activity and nonfarm pluriativa that promotes the appreciation of the environment, history, heritage and cultural diversity, while also contributing to the local economic and spatial reorganization, as well as with revitalization, to give new life to stagnant spaces aiming at preservation and enhancement, making it more attractive to visitors and providing improvements to the local population. The research is qualitative, exploratory and descriptive in-depth interviews with key informants and applied literature review relevant to the theme. The main objective of this research is to analyze the relationship of renovations in the municipality of Itaara with tourist activity. The categories were based on criteria Vaz (2006). The case study took place in the municipality of Itaara, the central region of Rio Grande do Sul, specifically in Road Perau and Pilgrimage and Feast of St. Expedite. The results obtained demonstrated improvements both for visitors and for the local population from the renovations occurred, noting that the local tourist offerings are analyzed Itaara. We conclude that rural tourism contributes to the revitalization process and provides improvements and benefits local communities and tourists. Understands the relationship with the revitalization of rural tourism in the sense that the revitalization is important not only to conserve environments or restore historic buildings, but also those related to favor spaces with multiple functions going where the benefits of rural tourism, both for visitors and the local population.